Nutrition and the homeless: the underestimated challenge. Issue 2 (28th June 2016) - Seale, J. V.; Fallaize, R.; Lovegrove, J. A.
Abstract: Homelessness is present in most societies and represents a situation in which the basic needs for survival including food are often limited. It is logical to surmise that the homeless person's diet is likely to be nutritionally deficient and yet there is a relative paucity in research regarding this issue with studies varying in both their methodology and homeless population. Despite these differences, diets of the homeless are frequently characterised as high in saturated fat and deficient in fibre and certain micronutrients, all of which can have negative implications for the homeless individual's health and/or mental state. The conclusion from intervention studies is that there is no consensus as to the most effective method for assessing dietary intake. In order to address this, the present review aims to provide a greater understanding of the existing literature surrounding nutrition and the homeless and to act as a foundation from which further research can be conducted. An evaluation of the main findings and challenges surrounding the assessment of the nutritional status of the homeless will be provided followed by a review of the physical and mental consequences of the homeless diet. Current and potential interventions aimed at increasing the nutritional quality of food consumed by the homeless will be addressed with a focus on the role of the nutritional science community in assisting in this endeavour.